2019
DOI: 10.5089/9781513516127.001
|View full text |Cite
|
Sign up to set email alerts
|

Do Financial Markets Value Quality of Fiscal Governance?

Abstract: We examine the link between the quality of fiscal governance and access to market-based external finance. Stronger fiscal governance is associated with improvements in several indicators of market access, including a higher likelihood of issuing sovereign bonds and having a sovereign credit rating, receiving stronger ratings, and obtaining lower spreads. Using the more granular information on quality of fiscal governance from Public Expenditure and Financial Accountability (PEFA) assessments for 89 emerging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Matadeen 2017conducted empirical research and argued that the determinants of stock market development include: macroeconomic determinants (real income, saving rate, financial development, inflation, interest rate and stock market liquidity) and institutional determinants (corruption, political rights, public sector efficiency, and regulatory burdens, legal protection of private property and law enforcement, but also the limits on political leaders). Keita et al (2019) conducted a complex empirical study on 89 emerging and developing economies, in order to investigate the linkage between the quality of fiscal governance and access to market-based external finance. The authors concluded that transparency of public finances, fiscal reporting, debt management and fiscal strategy are essential in improving credit ratings, issuing bonds, and obtaining lower cost of external financing.…”
Section: Introductionmentioning
confidence: 99%
“…Matadeen 2017conducted empirical research and argued that the determinants of stock market development include: macroeconomic determinants (real income, saving rate, financial development, inflation, interest rate and stock market liquidity) and institutional determinants (corruption, political rights, public sector efficiency, and regulatory burdens, legal protection of private property and law enforcement, but also the limits on political leaders). Keita et al (2019) conducted a complex empirical study on 89 emerging and developing economies, in order to investigate the linkage between the quality of fiscal governance and access to market-based external finance. The authors concluded that transparency of public finances, fiscal reporting, debt management and fiscal strategy are essential in improving credit ratings, issuing bonds, and obtaining lower cost of external financing.…”
Section: Introductionmentioning
confidence: 99%
“…9 Sovereign credit ratings were converted into numerical scores using the methodology used in Keita, Leon, and Lima (2019). A higher credit rating corresponds to a lower numerical score.…”
Section: Correlation Analysismentioning
confidence: 99%